Enriching traditional didactic teaching in undergraduate ophthalmology with lateral thinking method: a prospective study - Mohd Asyraaf, Abdul Kadir; Lim, Lik Thai (2022)
Purpose:To evaluate undergraduate medical students’ perspective on lateral thinking pedagogy in teaching clinical ocular anatomy in correlation to developing differential diagnoses and recognising red flags in managing common eye conditions.Methods:The prospective study compared the lateral thinking method (LTM) versus the traditional didactic method in teaching clinical ocular anatomy. Two hundred seventy‑two medical students who underwent ophthalmology clerkships were recruited over 3 years. They were randomised into two groups, the LTM and regular didactic groups. Students participated in pre and post‑tests to assess their theoretical clinical ophthalmic knowledge, and their responses to respective teaching methods were measured via the self‑assessment questionnaire (SAQ), which incor‑porated a five‑point Likert‑type scale.Results:Overall, the LTM group scored significantly higher than the control group, and they found the innovative teaching method improved their confidence and awareness in theoretical knowledge in generating differential diag‑noses, managing common eye conditions and recognising potential signs that could be sight and/or life‑threatening compared to the regular teaching group (P < 0.05). However, all students were neutral towards both lectures regard‑ing changing their negative perception of the current ophthalmic curriculum.Conclusion:From the student’s perspective, LTM is an effective tool in enriching regular teaching. The method encouraged versatile thinking patterns while enhancing the effectiveness of learning experience in time and resource‑limited undergraduate ophthalmic teaching.